Gamification Learning integrated with Local Wisdom based on Character Education, is There an Effect on Problem Solving Ability? - Dewi Satria Ahmar; Magfirah Magfirah; Detris Poba; Muhammad Fath Azzajjad (Jurnal Penelitian Pendidikan IPA, 2023)
The aim of this study was to determine the description of students' problem solving skills and the effect of gamification learning on students' problem solving ability. The population in this study consisted of 87 people. the research sample was selected based on purposive sampling technique so that the total sample in this study was 56 students who were divided into 2 classes, namely 28 people in the experimental class and 28 people in the control class. Students' problem solving ability was measured using a problem solving rubric developed by The Association of American Colleges and Universities (2017).Â  Data analysis used descriptive and inferential data analysis. The results of descriptive data analysis showed that the average value of the experimental class problem solving ability was 80.36 higher than the control class which was 72.86. The results of inferential data analysis with independent sample t-test showed that the significance value of the data was 0.001 (<0.05). Based on the research data, it can be concluded that there is an effect of gamification learning integrated with local wisdom based on character education on students' problem solving ability.